ANALISIS HERMENEUTIKA PADA PUISI “AKU INGIN” KARYA SAPARDI DJOKO DAMONO - filsa nirmawati; Teti Sobari; Dede Abdurakhman (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This article discusses hermeneutic analysis of the poem "Aku Ingin" by Sapardi Djoko Damono. The things discussed in this article are the meaning of the poem "Aku Ingin" by Sapardi Djoko Damono using the concept of hermeneutics, namely analyzing poetry with stages of meaning in accordance with the steps of hermeneutic analysis paul ricoeur. The stages are: 1) placing poetry as autonomous text; 2) classify the layers of symbols in poetry; 3) associating symbols with something outside the text; and 4) interpret the text. The measures aim to analyze the symbols contained in sapardi Djoko Damono's poem "Aku Ingin". Thus, this research can explain the meaning of poetry "Aku Ingin" more comprehensively. The results showed that hermeneutic analysis of sapardi Djoko Damono's poem "Aku Ingin" shows the use of symbols, wood, fire, and ash is a representation of efforts and efforts to achieve true love and simple love.